Pelatihan Penggunaan Aplikasi Guru Buddhis Digital untuk Guru Smb Vihara Buddha Dipasasana Lampung Timur - Rapiadi; Edi sumarwan; Mila wati; Benny saputra (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
This community service activity purposes to introduce the use of the digital Buddhist teacher application for SMB Buddhist temple teachers in Dipasasana, East Lampung, so that activities in education can be carried out properly. The target of dedication is the Buddhist monastery in Dipasasana, with a total of 5 participants. Service activities are carried out using various methods, ranging from surveys, focus group discussions, demonstrations, performances, and mentoring. The training materials provided include an introduction to digital Buddhist teacher applications. The results of the service activities show success, with indications in the form of high enthusiasm and motivation to utilize the participant's digital Buddhist teacher application at each stage of the training activity.